Implementation of STEAM Learning in Telling Aspects of Cognitive Development in Children Aged 5-6 Years at Al Ihsan Kindergarten, Cikande - Uswatun Hasanah; Nuryati Nuryati; Umalihayati Umalihayati (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This research is motivated by the learning implemented in schools is still conventional and monotonous, namely in the form of giving assignments to thicken letters, draw and color so that is does not stimulate children’s thinking skills. The study aims to describe the implementation of steam learning in developing aspects of cognitive development in children agen 5-6 years at Al Ihsan Cikande. The subjects of this study were 8 children. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation, the date were analyzed using Miles & Huberman’s model, which includes data reduction, data display, and conclusion drawing/verification. The research findings show that the application of STEAM learning through projeck-based play and the use of loose parts provides learning experiences that encourage children to think critically, logically, and symbolically, and to explore various ways of solving problems. This study concludes that STEAM learning provides meaningful learning experiences necessary to support the cognitive development of early childhood through active and exploratory learning processes.